Developing and maintaining intergenerational relationships in an economically vulnerable community: findings from the Flint women's study. (2nd November 2022) - Sneed, Rodlescia S.; Hailemariam, Maji; Key, Kent D.; Jordan, Tamara; Miller, Raven; Richie, Fallon; Robinson, DeWaun; Saddler, Sharon; Spencer, Bryan; Summers, Monicia; McCoy White, Jonne; Johnson, Jennifer E.
ABSTRACT: Few studies describe how community disadvantage impacts intergenerational relationships. Using interviews with women and service providers (n = 100), we explored benefits and challenges of intergenerational relationships in Flint, Michigan, an economically vulnerable community. Women valued relationships that increased social connections and generativity; however, few community resources promoted such relationships. Intergenerational relationships were important for leaving a social legacy in lieu of a meaningful economic legacy. Some middle-aged women are overwhelmed by caregiving, balancing employment while caring for multiple generations. Women desired intergenerational activities that include children and younger adult women. Further, caregiving programs should attend to the needs of middle-aged caregivers.